Arahan Penentuan Klaster Industri Pengembangan Rumput Laut di Kecamatan Mangarabombang, Kabupaten Takalar - Rizkiyah Amaliah Fadila; Ihsan Ihsan; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Takalar regency is one of three the biggest production of seaweed. The high amount of seaweed production is not comparable with the amount of seaweed produced caused seaweed is only sold in raw materials without being processed before. Therefore, the development of seaweed culture-based industrial clusters is needed with the aim of increasing the value of the product by considering the spatial aspects in order to be sustainable. The aim of this study is to identify the existing potential of seaweed commodities and determine the industry cluster of seaweed development. The location of this research was carried out in Takalar Regency specifically in Mangarabombang District and was carried out in January-March 2020 (3 months). The method used are a descriptive qualitative and spatial analysis in the form of an analysis of land suitability and carrying capacity of waters that refer to the indicators of seaweed industry cluster determination. The results showed the District of Mangarabombang was the highest producer of Euchemma Cottoni seaweed which was spread in Laikang Bay with the highest number of cultivators in the villages of Punaga and Laikang. Seaweed cultivation will be dried and distributed to the industry and local industry. The determination of industrial clusters is divided into 3 zones, Production zones is along the coastline of Mangarabombang District with an area of 2458,04 Ha, post-harvest zones located in Punaga Village, and processing zones located in Punaga, Laikang and Pattokappang Villages.